Combination prophylaxis in CMV high risk heart transplant recipients: A single center experience. Issue 3 (13th December 2022) - Van Aelst, Lucas N. L.; Droogné, Walter; Vörös, Gabor; Van Cleemput, Johan
Abstract: Introduction: Cytomegalovirus (CMV) is the most clinically relevant infectious agent following heart transplantation (HTX). Data on the beneficial effects of prophylactic use of CMV immunoglobulins (CMVIG) are scarce. Methods: In this single‐center, retrospective study, we reported patient outcomes following cardiac transplantation using prophylactic CMV treatment, including CMVIG. Distinct clinically relevant outcomes were compared across different CMV risk groups (CMV D−/R−, CMV D−/R+, CMV D+/R+, and CMV D+/R− or CMV high risk group). Results: We included 272 heart transplant procedures, performed between 1/1/2009 and 1/11/2020. Sixty‐one (22%) procedures belonged to the CMV high risk group, while 96 (35%), 50 (18%), and 65 (24%) were CMV D−/R−, CMV D−/R+, and CMV D+/R+, respectively. Baseline donor and recipient characteristics (sex, age, body mass index, cause of death, indication for HTX), ischemia times and baseline immunosuppressive regimens were similar across the different CMV risk groups, yet fewer patients were bridged with a mechanical circulatory support in the CMV D+/R− group. CMV disease following cardiac transplantation was more common in the CMV D+/R− risk group ( n  = 40 or 66.7%; p  < .001), yet mortality and re‐transplantation rates, cardiac allograft vasculopathy (CAV) severity, rejection episodes, and development of donor‐specific antibodies (DSA), post‐transplant lymphoproliferative diseases (PTLD), and EBV infections were similar across all four CMV risk groups. Conclusion: High risk CMV D+/R− patients had a similar survival compared to low and intermediate CMV risk groups using a prophylactic strategy combining CMVIG and viral DNA polymerase inhibitors. This may be related to a number of factors unrelated to prophylaxis strategy as two out of three CMV D+/R− recipients developed CMV primary infection after prophylaxis was discontinued.